Implementasi Gerakan Literasi Sekolah Pada Era New Normal di SMA Negeri 3 Banjarmasin - Destiana Nur Fitriani; Deasy Arisanty; Karunia Puji Hastuti; Muhammad Muhaimin; Aswin Nur Saputra (Universitas Lambung Mangkurat, 2022)
GLS is one of the efforts to make schools into learning organizations whose citizens are literate, but in this new normal era, school literacy activities carried out at SMA Negeri 3 Banjarmasin are quite hampered, so that it can make students reading interests decrease. The purpose of this study was to analyze the implementation of GLS in the new normal era at SMA Negeri 3 Banjarmasin. The research method used in this study uses a descriptive quantitative approach. Questionnaires were distributed to 36 teachers at SMA Negeri 3 Banjarmasin. The results of the research conducted indicate that the total score obtained from filling out 36 questionnaires is 1.869, so an average value of 51,9 is obtained, which corresponds to the level that refers to the Policy Research Center, Ministry of Education and Culture. It can be concluded that the score is 51,9 is at a moderate level (38-52), so the school literacy movement at SMA Negeri 3 Banjarmasin is included in the sufficient category.Keywords: Implementation, new normal, school literacy movement